Kim są „psy” w Ap 22,15? Lektura terminu οἱ κύνες w greckim antycznym kontekście kulturowym - Siemieniec, Tomasz Marcin (Verbum Vitae, 2021)
The presented article deals with the metaphor of “the dog” in Rev 22:15 on the cultural background of Ancient Greece. The analysis of the state of research has shown that exegetes interpreting the term οἱ κύνες refer primarily to parallel texts found in the Bible itself (and in extra-biblical religious literature). However, such an interpretation does not exhaust the richness of meaning of the metaphor of “the dog”. The same text read by Christians who have had a previous experience of Hellenistic culture opens up new ways for an exploration of new meanings of “the dog” metaphor. According to the author of the article, Christians originating from Hellenistic culture could see the motif of “the dog” in connection with pederastic courtship, where it was the embodiment of an older partner in this relationship – the so-called erastes. This understanding of the metaphor of “the dog” is based on the reference to hunting, which was an important part of the life of ancient Greeks. In Greek literature and in vase painting, when presenting the homosexual courtship of the elder – erastes towards the younger – eromenos, one often referred to the idea of hunting. This is evident in iconography, where scenes of pederasty often employ motifs of a dog, and in literature, where erastes’ efforts are depicted in the likeness of hunting. The author of the Apocalypse, placing “dogs” among the categories of people excluded from participation in the New Jerusalem, showed that pederastic practices prevent access to the community of God's new people.